2017
DOI: 10.1128/mmbr.00066-16
|View full text |Cite
|
Sign up to set email alerts
|

Effectors of Filamentous Plant Pathogens: Commonalities amid Diversity

Abstract: Fungi and oomycetes are filamentous microorganisms that include a diversity of highly developed pathogens of plants. These are sophisticated modulators of plant processes that secrete an arsenal of effector proteins to target multiple host cell compartments and enable parasitic infection. Genome sequencing revealed complex catalogues of effectors of filamentous pathogens, with some species harboring hundreds of effector genes. Although a large fraction of these effector genes encode secreted proteins with weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
163
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 116 publications
1
163
0
9
Order By: Relevance
“…In plants, perception of PAMPs or effectors activates a complicated signal transduction network, including mitogen‐activated protein kinase (MAPK) cascades, and/or chemical signalling by plant hormones and transcriptional regulation via transcription factors (Pitzschke et al , ; Wang et al ., ). The immune activation culminates in a series of physiological changes in the plant, such as reactive oxygen species (ROS) production, cell wall fortification, and the localized rapid cell death known as the hypersensitive response (HR) (Ingle et al , ; Franceschetti et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, perception of PAMPs or effectors activates a complicated signal transduction network, including mitogen‐activated protein kinase (MAPK) cascades, and/or chemical signalling by plant hormones and transcriptional regulation via transcription factors (Pitzschke et al , ; Wang et al ., ). The immune activation culminates in a series of physiological changes in the plant, such as reactive oxygen species (ROS) production, cell wall fortification, and the localized rapid cell death known as the hypersensitive response (HR) (Ingle et al , ; Franceschetti et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that hybridization and introgression enabling pathogens to expand their host ranges is more common than previously thought (Lemaire et al, 2015;Depotter et al, 2016;Menardo et al, 2016). In comparison to a large number of evolutionarily young effectors, relatively few effectors are conserved across fungal taxa (Kohler et al, 2016;Franceschetti et al, 2017). Coevolution between hosts and pathogens led to the diversification of specific fungal effectors across pathogen lineages (Jiang et al, 2008;Huang et al, 2014;Sperschneider et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three PSR1‐like effectors (PcPSR1L, PiPSR1L and PpPSR1L) found in Phytophthora species shared conserved biological functions with PSR1, but did not bind to PINP1 or PINP1 homologs in their host plants in the Y2H assay (Fig. S4a,b), suggesting that PSR1 and PSR1‐like effectors share a similar function and conserved WY domain; however, they are not real orthologous effectors, they might suppress RNA silencing and contribute to infection by binding to different host targets (Franceschetti et al ., ). Together, these findings expand our understanding of oomycete WY domain effectors, which possess structural flexibility and diverse biological functions to suppress plant immunity.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these findings suggest that rapid evolution of the protein sequence encoding the WY motif led to diversification of these effectors. This in turn may have facilitated the acquisition of new effector functions and evasion from host immunity pathways (Franceschetti et al ., ).…”
Section: Introductionmentioning
confidence: 97%